2009
DOI: 10.4269/ajtmh.2009.80.896
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Intestinal Helminth Co-infection Among Pregnant Women in Ghana: Prevalence and Risk Factors

Abstract: Both malaria and intestinal helminths are endemic in sub-Saharan Africa, and their co-infection occurs commonly. This cross-sectional study assessed the prevalence of malaria and intestinal helminth co-infection in a sample of > 700 pregnant women in Ghana and identified risk factors for co-infection. The prevalence of malaria infection, intestinal helminth infection(s), and co-infection was 36.3%, 25.7%, and 16.6%, respectively. Women with intestinal helminth infection(s) were 4.8 times more likely to have ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 41 publications
12
85
9
Order By: Relevance
“…This was a cross-sectional study of women presenting for delivery at two hospitals in Kumasi, the Komfo Anokye Teaching Hospital (KATH) and the Manhyia Polyclinic, between November and December 2006. As described in an earlier report, 12 all women who had a singleton, uncomplicated pregnancy were identified from admission records and invited to participate. Women who had a multiple or complicated pregnancy, who were positive for syphilis, who had hemoglobinopathy, or infections known to affect maternal health or birth outcome were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was a cross-sectional study of women presenting for delivery at two hospitals in Kumasi, the Komfo Anokye Teaching Hospital (KATH) and the Manhyia Polyclinic, between November and December 2006. As described in an earlier report, 12 all women who had a singleton, uncomplicated pregnancy were identified from admission records and invited to participate. Women who had a multiple or complicated pregnancy, who were positive for syphilis, who had hemoglobinopathy, or infections known to affect maternal health or birth outcome were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Although iron deficiency anemia (IDA) is the most common cause of anemia in pregnant women, there are many other causes including nutritional causes such as folate, vitamin B 12 , and vitamin A deficiencies, infective causes such as malaria, and intestinal helminth infections, ineffective erythropoiesis, severe hemorrhage, hemoglobinopathies, chronic diseases, G6PD deficiency, and hemolytic anemia from drugs or toxins. 8,[11][12][13] Consequently, any assessment of the cause of anemia must put these into consideration to delineate cause-specific etiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study methods have been described elsewhere. 24 Briefly, a cross-sectional study was conducted in Kumasi, Ghana. All women presenting for delivery in November or December 2006 at one of two large hospitals were asked to participate in the study if they had a singleton, uncomplicated pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Yatich et al 13 in Ghana and Basavaraju et al 14 in Jos, Nigeria reported high hookworm and malaria co-infection, supposedly due to the wider thermal tolerance of hookworm eggs compared to those of Ascaris lumbricoides and Trichuris trichiura. In this study however, a higher association between malarial parasites and Ascaris lumbricoides was observed, possibly because it is the most prevalent helminth amongst children.…”
Section: -43mentioning
confidence: 99%